2014
DOI: 10.1152/japplphysiol.01027.2013
|View full text |Cite
|
Sign up to set email alerts
|

Plasma K+dynamics and implications during and following intense rowing exercise

Abstract: We investigated whether potassium (K(+)) disturbances during and following intense exercise may be pronounced when utilizing a large contracting muscle mass, examining maximal 2,000-m rowing exercise effects on radial arterial plasma K(+) concentration ([K(+)]a) in 11 healthy adults. Blood was sampled at baseline, preexercise, each 30 s during rowing, and for 30 min postexercise. Time to complete 2,000 m was 7.26 ± 0.59 min; power output at 30 s was 326 ± 81 W (mean ± SD). With exercise time expressed in decil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 55 publications
3
21
0
Order By: Relevance
“…The antecubital venous [K + ] reported during intense intermittent exercise varies, reaching 4.3 mM during squash (Struthers et al 1988), 5.1 mM during soccer (Krustrup et al 2006), and 5.5-6 mM during repeated intermittent sprint testing (Wylie et al 2013;Mohr et al 2011;Mohr et al 2007;Duffield and Marino 2007;Mohr et al 2006 O 2 peak for use on the same cycle ergometer in the subsequent experimental trials. All respiratory measurements were as previously described (Atanasovska et al 2014) . Heart rate and rhythm were monitored at rest and during incremental exercise using a 12-lead ECG (Model X-Scribe Stress Test System, Mortara Instrument Inc, Milwaukee, WI, USA).…”
Section: Introductionmentioning
confidence: 99%
“…The antecubital venous [K + ] reported during intense intermittent exercise varies, reaching 4.3 mM during squash (Struthers et al 1988), 5.1 mM during soccer (Krustrup et al 2006), and 5.5-6 mM during repeated intermittent sprint testing (Wylie et al 2013;Mohr et al 2011;Mohr et al 2007;Duffield and Marino 2007;Mohr et al 2006 O 2 peak for use on the same cycle ergometer in the subsequent experimental trials. All respiratory measurements were as previously described (Atanasovska et al 2014) . Heart rate and rhythm were monitored at rest and during incremental exercise using a 12-lead ECG (Model X-Scribe Stress Test System, Mortara Instrument Inc, Milwaukee, WI, USA).…”
Section: Introductionmentioning
confidence: 99%
“…The second important finding was that after the second Ice Mile, there was an increase of [K + ] from 5.6 mM to 6.9 mM. This could be explained by a K +shift from the muscle cells as shown in a study following intense rowing exercise where plasma [K + ] increased within the first 90 sec and remained high during the exercise (2,11,12). Another study regarding the consequences and dynamics in potassium shifts concluded that a rapid and pronounced increase of [K + ] and a substantial loss of [K + ] from the active skeletal muscle were very likely primary causes of fatigue with a fast recovery (29).…”
Section: Blood Parametersmentioning
confidence: 85%
“…The effects of a decreased natriuresis after cold immersion and hypothermia, and changes in H + should also be considered as cause of secondary changes in pH and [K + ] (33). However, this finding requires further investigation (2,16). A systematic review of swimming-related deaths suggested that cardiac arrhythmias were the most likely etiology of a swimming-related death (1).…”
Section: Blood Parametersmentioning
confidence: 96%
See 1 more Smart Citation
“…As a consequence, the extracellular concentrations of ions deviate from plasma concentrations, protecting the brain against physiological or pathophysiological variations in plasma potassium, calcium and magnesium levels [16]. Indeed blood potassium concentrations can increase to >6 mM during exercise [37], while calcium and magnesium concentrations can drastically decrease during different diseases and during eclampsia [38]. A myriad of transport mechanisms acts across endothelial cells [6], and transendothelial transport through brain capillaries is generally smaller than in peripheral capillaries [39].…”
Section: Blood-brain Barrier -Morphology and Transport Mechanismsmentioning
confidence: 99%